1998
DOI: 10.3177/jnsv.44.113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soy Protein Isolate (SPI) and Casein on the Postprandial Lipemia in Normolipidemic Men.

Abstract: SummaryTo elucidate the effects of soybean protein and casein on postprandial lipemia, oral fat load tests were performed before and 3 weeks after the administration of soy protein isolate (SPI) and casein supplement to normolipidemic men. Eleven normolipidemic male subjects on otherwise identical controlled diets were assigned to either a 20g/d soy protein isolate (SPI) dietary supplement or a casein dietary supple ment for three weeks in a crossover design. Fat load tests with 40g/m2 of bovine milk fat were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…supplementation on select fasting and postprandial blood lipid and glucose concentrations in normocholesterolemic, sedentary males. Our data support the hypothesis that the postprandial state is more sensitive than the traditional lipid profile for detecting changes associated with soy consumption in this study population, which is in concurrence with previous data [48]. While fasting blood lipid and glucose concentrations did not change significantly, postprandial TAG concentration was surprisingly higher after Soy-consumption.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…supplementation on select fasting and postprandial blood lipid and glucose concentrations in normocholesterolemic, sedentary males. Our data support the hypothesis that the postprandial state is more sensitive than the traditional lipid profile for detecting changes associated with soy consumption in this study population, which is in concurrence with previous data [48]. While fasting blood lipid and glucose concentrations did not change significantly, postprandial TAG concentration was surprisingly higher after Soy-consumption.…”
Section: Discussionsupporting
confidence: 92%
“…These data suggest that the dearth of isoflavones in Soy-may deleteriously alter postprandial processing of TAG such that over time risk for CVD potentially increases. Together, with a previous report, our data show support for measuring blood lipids in a postprandial state in order to detect changes with soy ingestion [48]. However, these changes are minimal at best in the normocholesterolemic, sedentary male, which provides credence to a recent statement by the American Heart Association; which iterated that the ingestion of soy products provides little additional, salubrious benefit beyond the typical vegetarian diet [44].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Dietary fiber [16,17], glucose [18], soybean protein [19] and exercise [20,21] have been shown to reduce the magnitude of postprandial lipemia. Several recent studies have also demonstrated the acute effects of dietary fatty acids on postprandial lipemia [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, remnant-like particles (RLP), which is the lipoprotein unbound to the immunoaffinity chromatog raphy that consists of monoclonal antibodies to apoB -100 and to apoA-1, has been used as a marker of rem nant lipoproteins (6). We have previously reported that 20g per day of SPI intake for 3 weeks improved the me tabolism of postprandial remnant lipoproteins after an oral fat load compared with casein intake and slightly reduced the fasting of RLP cholesterol, which was not significant (7). Therefore the effect of soy protein on TG or remnant lipoproteins is unclear.…”
mentioning
confidence: 99%